Lymphatic endothelium contributes to colorectal cancer growth via the soluble matrisome component GDF11. Issue 7 (9th April 2019) - Ungaro, Federica; Colombo, Piergiuseppe; Massimino, Luca; Ugolini, Giovanni Stefano; Correale, Carmen; Rasponi, Marco; Garlatti, Valentina; Rubbino, Federica; Tacconi, Carlotta; Spaggiari, Paola; Spinelli, Antonino; Carvello, Michele; et al.
Abstract : Colorectal cancer (CRC) is one of the most malignant tumors worldwide. Stromal cells residing in the tumor microenvironment strongly contribute to cancer progression through their crosstalk with cancer cells and extracellular matrix. Here we provide the first evidence that CRC‐associated lymphatic endothelium displays a distinct matrisome‐associated transcriptomic signature, which distinguishes them from healthy intestinal lymphatics. We also demonstrate that CRC‐associated human intestinal lymphatic endothelial cells regulate tumor cell growth via growth differentiation factor 11, a soluble matrisome component which in CRC patients was found to be associated with tumor progression. Our data provide new insights into lymphatic contribution to CRC growth, aside from their conventional role as conduits of metastasis. Abstract : What's new? Stromal cells residing in the tumor microenvironment strongly contribute to tumor progression through their crosstalk with cancer cells and extracellular matrix (ECM). In this study, the authors demonstrate that colorectal cancer (CRC)‐associated human intestinal lymphatic endothelial cells (HILEC) regulate tumor cell growth via the soluble matrisome component Growth Differentiation Factor 11 (GDF11), pointing to an unconventional role of lymphatics in controlling CRC growth and progression aside from their classical role as conduit of metastasis. The findings pave the way for new studies ultimately aiming at the identification of GDF11 inhibitors for the treatment of CRC in its early phases.